Ralvenia, a new genus of ennomine moth from the Americas with cryptic species diversity (Lepidoptera: Geometridae) - Matson, Tanner A.; Hallwachs, Winnie; Janzen, Daniel H. (Zootaxa, 2026)
Ralvenia Matson gen. nov. is established to accommodate a lineage of ennomine moths that includes several undescribed cryptic species and others formerly assigned to four unrelated genera. The following new combinations are proposed: Ralvenia accentuata (Barnes & McDunnough) comb. nov. (transferred from Prochoerodes Grote); Ralvenia cervina (Warren) comb. nov. and Ralvenia cervinoides (Schaus) comb. nov. (both transferred from Periclina Guenée); Ralvenia arge (Druce) comb. nov. (transferred from Sabulodes Guenée); and Ralvenia lapa (Dognin) comb. nov. (transferred from Certima Walker). Four new species are described: Ralvenia dactyvalva Matson sp. nov., Ralvenia hamifurca Matson sp. nov., Ralvenia nuda Matson sp. nov., and Ralvenia serrata Matson sp. nov. Adults and male and female genitalia are illustrated. The larva of Ralvenia cervinoides is illustrated. DNA barcode data, when available, are reviewed for each species.